A contrastive analysis of reports on US Military withdrawing from Afghanistan: China Daily and U.S. News & World Report - Li, Jiayu (Universitas Ahmad Dahlan, 2024)
This article studies new reports released by the U.S. and China press from 30 August to 2 September 2021 on the United States’ troops withdrawing from Afghanistan, aiming at investigating the difference of ideologies towards the evacuation. Comparing how China Daily and U.S. News & World Report reported the withdrawal, the study finds out that invidious terminology isn’t presented in the U.S. reports but repugnant terms are presented in China reports in the headlines. Moreover, the chaotic withdrawal is just Biden’s failure and there is no mention of the death of Afghans at all in the U.S. press, while the withdrawal is the U.S. failure but also their so-called “war on terror” is pointless from the beginning, moreover the “America First” policy is implied in China reports. Taoist philosophy (Tao Te Ching) has been reflected in China reports.